The Development of LKPD With an Insight in The Character of Tolerance in Citizenship Education Subjects in Class IV State Primary School 101783 Saentis - Azly, Mutiara (Journal of General Education Science, 2023)
This research aims to develop a product in the form of a Student Worksheet (LKPD) with an insight into the character of tolerance in the Citizenship Education subject in class IV at SD Negeri 101783 Saentis. The LKPD is adjusted and prepared with steps in the cooperative learning model, material in the form of the cultural diversity of my people which is packaged in character education questions. The development of this LKPD was carried out using the R&D (Research & Development) method, using a 3D model. The 3D development model consists of define, design and develop. This research was only carried out until the development stage because the researcher did not aim to find out the effectiveness of the product that had been developed. The feasibility results for the LKPD insight into the character of tolerance obtained were very good overall. The material expert validation assessment is 90% with a very valid category. The results of the design expert validation assessment were 86.9% with a very valid category. And the results of the language expert validation assessment were 96.65% with a very valid category. The results of the practicality assessment by the teacher were 95.9% with very practical criteria and the results of the practicality assessment by students were 83.2% with the very practical category, so that the LKPD is suitable for use in the elementary school (SD) environment.